2019
DOI: 10.1088/1361-6471/ab096d
|View full text |Cite
|
Sign up to set email alerts
|

Hidden charm pentaquarks: mass spectrum, magnetic moments and photocouplings

Abstract: We develop an extension of the usual three flavor quark model to four flavors (u, d, s and c), and discuss the classification of pentaquark states with hidden charm (qqqcc). We fit our model to the known baryon spectrum and we predict the double and triple charm baryons, finding good agreement with the most recent lattice QCD calculations. We compute the the ground state of hidden charm pentaquarks and their associated magnetic moments and electromagnetic couplings, of interest to pentaquark photoproduction ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 92 publications
(369 reference statements)
0
33
0
Order By: Relevance
“…These SU(3) submultiplets belong to the ½421 irreducible representation of SU(4) of dimension 140. The members of the irreducible representation denoted by 140 can have a spin value of either 1=2 or 3=2 [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These SU(3) submultiplets belong to the ½421 irreducible representation of SU(4) of dimension 140. The members of the irreducible representation denoted by 140 can have a spin value of either 1=2 or 3=2 [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[22,38] using the following two conditions: (i) the pentaquark wave function should be a color singlet and (ii) the wave function of the four-quark subsystem should be antisymmetric. The permutation symmetry of four-quark states is characterized by the S 4 Young tableaux [4], [31], [22], [211] and [1111] or, equivalently, by the irreducible representations of the tetrahedral group T d (which is isomorphic to S 4 ) as A 1 , F 2 , E, F 1 and A 2 , respectively. The first condition that the pentaquark wave function has to be a color-singlet, implies that the color wave function of the four-quark configuration has to be a [211] triplet with F 1 symmetry under T d .…”
Section: Pentaquark Statesmentioning
confidence: 99%
“…In Ref. [22] it was shown that there are in total seven uudcc ground-state pentaquark configurations with angular momentum and parity J P = 3/2 − (which is quoted in the literature as the most likely value of the angular momentum and parity of the P c pentaquark [1]), three of which belong to a flavor decuplet and the remaining four to a flavor octet (see Fig. 1 and first column of Table 1).…”
Section: Pentaquark Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Group theory approach has been applied to construct the pentaquark wave functions and study the role of pentaquark components in baryon [4][5][6][7][8][9][10][11]. However, the construction of high-order spatial wave functions of pentaquark states in various permutation symmetries has been a challenge.…”
Section: Introductionmentioning
confidence: 99%